WORKSHOPPRACTICE, ENTREPRENEURAL TRAINING AND SKILL ACQUISITION FOR VOCATIONAL ENTERPRISES AMONG STUDENTS IN ABRAHAM ADESANYA POLYTECHNIC, IJEBU-IGBO - Edun, Hakeem J.; Oduwole, Oduwole Abiodun; Chidubem, Mordi Augustine; Omowumi, Daramola Elizabeth; Temitayo, Kuyoro Agnes (African Journal of Behavioural and Scale Development Research, 2024)
This study investigated workshop practice and entrepreneurial training in fostering skill acquisition among polytechnic students in Ogun state. The study employed a survey research design, a sample of sixty (60) students was used. Descriptive and simple percentage was utilized while the analysis of variance was used to test the hypothesis at 0.05 level of significance. The findings of the study showed that Workshop practices have any significant contributions on skill acquisition among polytechnic students. It also reveals that there is significant influence of entrepreneur training on skill acquisition among polytechnic students. There is no significant gender differences on workshop practice and entrepreneurial training in fostering skills acquisition among polytechnic students. The study recommended that the curriculum of the polytechnic students should intensified to ensure that it will give room for enduring workshop practice and entrepreneurial training